2007
DOI: 10.1164/rccm.200606-828oc
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Severe Pulmonary Emphysema

Abstract: Rationale: Limited data on sex differences in advanced COPD are available. Objectives: To compare male and female emphysema patients with severe disease. Methods: One thousand fifty-three patients (38.8% female) evaluated for lung volume reduction surgery as part of the National Emphysema Treatment Trial were analyzed. Measurements and Main Results: Detailed clinical, physiological, and radiological assessment, including quantitation of emphysema severity and distribution from helical chest computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
222
5
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(253 citation statements)
references
References 69 publications
21
222
5
5
Order By: Relevance
“…1). This is different from what is seen in severe COPD subjects, whose emphysema was less peripheral in females, because the radial distribution of emphysema may have a functional impact, it was suggested that such difference likely accounted for the lower diffusing capacity of the lung for carbon monoxide (DL,CO) observed in females [8]. Unfortunately, we could not explore such morphological-functional relationships as the DL,CO was not part of our lung screening project.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…1). This is different from what is seen in severe COPD subjects, whose emphysema was less peripheral in females, because the radial distribution of emphysema may have a functional impact, it was suggested that such difference likely accounted for the lower diffusing capacity of the lung for carbon monoxide (DL,CO) observed in females [8]. Unfortunately, we could not explore such morphological-functional relationships as the DL,CO was not part of our lung screening project.…”
Section: Discussionmentioning
confidence: 75%
“…Our findings substantially mirror and extend those reported in patients with COPD. Thus, an analysis limited to severe emphysematous patients from the National Emphysema Trial [8], showed that emphysema in females, relative to males, was less extensive and characterised by smaller hole size, but less peripheral involvement on CT. Furthermore, DRANSFIELD et al [15] demonstrated that females had less severe emphysema at all stages of COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women are suggested to be more susceptible to the effects of tobacco smoke and therefore are at higher risk of developing COPD 10 . Some studies have found structural differences within the lungs, with men having more emphysema than women [11][12][13] while others have found that in women the walls of the small airways are thicker 13 .…”
Section: Background Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%